Improving solar water-splitting performance of LaTaON2 by bulk defect control and interface engineering - Huang, Huiting (2020)
Particle-assembled photoanode films for solar water splitting are often subjected to serious electron-hole recombination, thus exhibiting low solar-to-hydrogen efficiency. The construction of efficient particle-assembled photoanode remains a challenge. Here, taking LaTaON2 particle-assembled photoanode as a model, bulk defect control and interface engineering were introduced to reduce the electron-hole recombination. As a result, the solar photocurrent of LaTaON2 achieves 2.1 mA cm−2 at 1.6 VRHE after the modification of CoOx, an order of magnitude greater than the previously-reported value of 0.15 mA cm−2. This dramatic enhancement is mainly ascribed to increased bulk electrical conductivity, and less back reactions on the conductive substrates, as well as facilitated hole transfer to reaction sites. This study may provide guidelines for the construction of highly efficient particle-assembled photoanode films.